Residential environment and breast cancer incidence and mortality: a systematic review and meta-analysis - Akinyemiju, Tomi F (BMC Cancer, 2015)
BACKGROUND: Factors beyond the individual level such as those characterizing the residential environment may be important to breast cancer outcomes. We provide a systematic review and results of meta-analysis of the published empirical literature on the associations between breast cancer risk and mortality and features of the residential environment. METHODS: Using PRISMA guidelines, we searched four electronic databases and manually searched the references of selected articles for studies that were published before June 2013. We selected English language articles that presented data on adult breast cancer incidence or mortality in relation to at least one area-based residential (ABR) independent variable. RESULTS: We reviewed 31 eligible studies, and observed variations in ABR construct definition and measurement, study design, and analytic approach. The most common ABR measures were indicators of socioeconomic status (SES) (e.g., income, education, summary measures of several SES indicators or composite SES). We observed positive associations between breast cancer incidence and urbanization (Pooled RR for urban vs. rural: 1.09. 95% CI: 1.01, 1.19), ABR income (Pooled RR for highest vs. lowest ABR income: 1.17, 95% CI: 1.15, 1.19) and ABR composite SES (Pooled RR for highest vs. lowest ABR composite SES: 1.25, 95% CI: 1.08, 1.44). We did not observe consistent associations between any ABR measures and breast cancer mortality. CONCLUSIONS: The findings suggest modest positive associations between urbanization and residential area socioeconomic environment and breast cancer incidence. Further studies should address conceptual and methodological gaps in the current publications to enable inference regarding the influence of the residential environment on breast cancer.